Integrity Assessment of Cracked Pressure Vessel with Considering Effect of Residual Stress Based on Failure Assessment Diagram Criteria - Akbar, Musthafa; Setiawan, Rachman (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2016)
During the period of its operation, a pressure vessel may experience excessive loading which can cause crack defects. Integrity analysis needs to be carried out to evaluate the feasibility operation of that cylindrical pressure vessel with defects. In this paper, integrity assessment of cracked pressure vessel under internal pressure and tensile residual stress was conducted based on failure assessment diagram criteria. This criteria applied widely and adopted in API 579-1/ASME FFS-1 2007 Code. There are three assessment levels provided in code. Level 1 and 2 assessment performed using analytical calculation while Level 3 assessment is conducted using finite element method. On a case study, failure criteria for the integrity analysis is based on the Failure Assessment Diagram (FAD), that distinguish safe and unsafe region based on two failure criteria, namely brittle fracture and ductile fracture. This diagram is built using finite element method with the assumptions of both Linear Elastic Fracture Mechanics (LEFM) and Elastic Plastic Fracture Mechanics (EPFM). Based on Level 1 assessment, the pressure vessel under study is not recommended to be operated, whilst based on Level 2 and 3 assessments the pressure vessel is considered acceptable. This study concludes that Level 1 and 2 analysis provide more conservative results when compared with level 3 analysis. Failure Assessment Diagram for Level 3 analysis relatively more conservative at elastic-plastic region (0.4<Lr<1), but less conservative at plastic collapse region. Parametric studies performed with increasing operating pressure and size of defects. Based on analysis, failures of the pressure vessel occur at pressure of 403 psi and an aspect ratio of 0.18 for analysis with including the effect of tensile residual stresses. Meanwhile, if the analysis is done by ignoring the effect of residual stress, pressure vessel failed at pressure of 589 psi and leak when aspect ratio reaching 0.42.